Stages and Main Problems of the Century-Long Control Theory and System Identification Development. Part 5. Principles and Problems in Control and Identification of Complex Systems of Various Nature Based on Cognitive Maps Impulse Processes Models - Romanenko, V.; Gubarev, V.; Miliavskyi, Yu. (Проблеми керування та інформатики, 2024)
The article provides a review and generalization of the principles, methods, and problems of designing discrete controllers for controlling complex systems of various nature, whose dynamics are described using difference equations of cognitive maps (CM) impulse processes (Roberts equations). An external control vector is implemented by discrete controllers based on varying node coordinates or weight coefficients of CM; the controllers are designed based on well-known methods of control theory. The article provides solutions to the following problems: stabilization of unstable impulse processes in CM of complex systems, control by varying weight coefficients, coordinating control of ratios between node coordinates, suppression of external disturbances, modeling impulse processes with multirate sampling of node coordinates, and identification of weight coefficients in CM impulse process models with complete and incomplete data. У статті наведено огляд та узагальнення принципів, методів і проблем проектування дискретних регуляторів для керування складними системами різної природи, динаміка яких описується рівняннями різниць когнітивних карт (імпульсні процеси, рівняння Робертса). Зовнішній вектор керування реалізується дискретними регуляторами шляхом варіювання координат вузлів або вагових коефіцієнтів когнітивних карт; регулятори проектуються на основі відомих методів теорії керування. Розглянуто задачі стабілізації нестійких імпульсних процесів у когнітивних картах складних систем, керування процесами за допомогою варіювання вагових коефіцієнтів, а також координаційне керування співвідношеннями між координатами вузлів. Запропоновано методи придушення зовнішніх збурень, моделювання імпульсних процесів із багаторівневим відбором координат вузлів та ідентифікації вагових коефіцієнтів у моделях імпульсних процесів когнітивних карт за повними та неповними даними.